Comparison of modified agonist, mild-stimulation and antagonist protocols for in vitro fertilization in patients with diminished ovarian reserve. Issue 6 (June 2018) - Yu, Rong; Jin, Hao; Huang, Xuefeng; Lin, Jinju; Wang, Peiyu
Objective: To compare the efficacy of three protocols for ovarian stimulation in patients with diminished ovarian reserve during in vitro fertilization (IVF) treatment. Methods: This prospective randomized study enrolled patients with diminished ovarian reserve who underwent cycles of IVF or intracytoplasmic sperm injection. The patients were randomly divided into three groups: a modified gonadotrophin releasing hormone (GnRH) agonist protocol (group A); (ii) a mild stimulation protocol (group B); or (iii) an antagonist protocol (group C). Demographic characteristics, clinical variables and pregnancy outcomes were compared between the groups. Results: A total of 116 patients were enrolled in the study: 54 in group A, 52 in group B and 60 in group C. Group B (32.69%) had a significantly higher cycle cancellation rate compared with groups A (11.11%) and C (16.67%). The early abortion rate of group C (44.44%) was significantly higher than group A (12.50%), but not significantly different from group B (16.67%). There were no significant differences in the clinical pregnancy rates and live birth rates among the three groups. Conclusion: A modified GnRH agonist protocol achieved a comparable pregnancy rate to those of the mild stimulation protocol and antagonist protocol, whilst having lower cycle cancellation and early abortion rates.